3D Hippocampal Place Field Dynamics in Free-Flying Echolocating Bats - Wohlgemuth, Melville J.; Yu, Chao; Moss, Cynthia F. (Frontiers in Cellular Neuroscience, 2018)
The storage and retrieval of memories operate in a wide range of natural behaviors, such as foraging, mating and navigating. A large body of laboratory research has investigated the process by which environmental cues are acquired and used for spatial navigation in rodents; however, the key to differentiating between species specializations and general principles lies in comparative research. Research has focused on a class of neurons in the hippocampus implicated in the representation of allocentric space – termed place cells – and the process by which these representations form. Many models of hippocampal place field formation depend on continuous theta, a low frequency brain oscillation that is prevalent in crawling rodents. Comparative studies of hippocampal activity in echolocating bats have reported many findings that parallel the rodent literature, but also noteworthy species differences, especially with respect to theta rhythm. Here we review studies of the bat hippocampal formation and point to gaps in our knowledge, which motivate new lines of inquiry. We present new data from the free-flying laryngeal echolocating big brown bat, which shows, similar to the lingual echolocating Egyptian fruit bat, 3-D place cells, without continuous theta. We also show new data, which demonstrate that the animal’s control over echolocation call rate (sensory sampling) influences place field tuning. These results motivate future comparative research to understand the intersection of natural behaviors and hippocampal function.